(untitled) (UUM Journal of Legal Studies, 2025)
Lex sportiva is a fundamental legal principle in sports law that emphasises autonomy in regulating and enforcing law in sports. The sports law in Indonesia has not yet accommodated the aspect of lex sportiva, failing to guarantee legal certainty and affecting the suboptimal regulation and enforcement of law in sports. This research aims to analyse the position of lex sportiva in sports law and the state’s authority in sports, as well as the implications and future regulation for strengthening this principle. This is doctrinal legal research employing conceptual and statutory approaches. The findings of this research indicate that the position of the lex sportiva principle in sports law is associated with the state’s authority in the field of sports, which potentially causes conflicts between laws made by a sport and by the state in organising sports. The practical implication is that implementing the lex sportiva principle in sports law may lead to legal uncertainty due to too much state intervention in sports-related arrangements in Indonesia. This research is expected to contribute to future regulatory efforts related to the affirmation of the principle in this context. Moreover, strengthening the lex sportiva principle in Sports Law and the Indonesian sports legal system can be done by revising the Sports Law and providing interpretation by the Constitutional Court, which involves the judicial review process.